Biology concepts and connections - Campbell, Neil A.; Reece, Jane B. ; Taylor, Martha R. ; Simon, Eric J. ; Dickey, Jean L. (San Francisico, CA, 2009)
Is a widely acclaimed introductory biology textbook designed for non-majors. It presents core biological principles through a modular format that integrates clear explanations with engaging illustrations, emphasizing the relevance of biology to everyday life
Keywords: Biology